A113 WHAT IS A FLARE OF IBD? THE MANITOBA LIVING WITH IBD STUDY. (1st March 2018) - Witges, K; Targownik, L E; Haviva, C; Sexton, K; Walker, J R; Graff, L A; Lix, L; Miller, N; Bernstein, C N
Abstract: Background: Persons with IBD and their clinicians often use the term 'flare' to refer to a presumed disease worsening. Instruments used to identify a patient-defined IBD flare are limited. Aims: A case-control design was used to assess the relationship between a 7-point indicator used to identify an IBD flare and alternative measures of disease activity and quality of life: fecal calprotectin (FCAL), a 2-point self-report scale defining IBD as inactive/active, a newly developed symptom index score (SIBDSI), and the short form IBDQ (SIBDQ). Methods: Persons aged 18–75 living in Manitoba with a confirmed IBD diagnosis (n=71) were surveyed biweekly for 26 weeks (98% response rate), and provided periodic stool samples. A patient-defined IBD flare was identified using a score of 6 or 7 on the 7-point indicator; a dynamic measure assessing change in symptoms over time. Participants with self-defined flares were systematically matched to controls (participants who had never reported a flare) based on survey week, sex, and disease type. We compared the prevalence of active IBD symptoms using the SIBDSI and the SIBDQ. We also compared SIBDSI and SIBDQ scores for both flares and controls at the time of and two weeks prior to the reported flare, to determine if the patient-identified flare reflected a change in symptom activity. A FCAL level ≥ 150 was indicative of intestinal inflammation. Results: 38% of participants reported at least one IBD flare during the study period. 97.2% of persons reporting a flare described having active IBD compared with 32.4% of controls (p<0.001). 94.4% of persons reporting a flare vs 38.2% of controls had an SIBDSI score above the cut-off of 14 for CD; 13 for UC (p<0.001). The mean SIBDSI score was significantly different in flares versus controls (31.1 ± 12.0 vs 11.9 ± 7.5, p<0.001), as was the mean SIBDQ score (44.3 ± 9.1 vs 57.0 ± 9.1, p<0.001). There was a greater change in SIBDSI and SIBDQ scores among flares than among controls, comparing two weeks prior and the time of the reported flare (SIBDSI Δ=8.61 ± 8.37 vs 0.27 ± 3.94; SIBDQ Δ=6.22 ± 5.27 vs 0.45 ± 3.36; p<0.001 for both. Participants in the flare group were no more likely than matched controls to have an elevated FCAL (52.9% vs. 47.1%, p=0.825) at the time of the reported flare. Conclusions: The presence of a self-reported flare was associated with higher levels of symptom activity and lower health related quality of life. Changes in symptoms and quality of life concurrent with the report of a flare, provided confirmation of the patient experience. While FCAL levels did not differentiate those reporting a flare from those not, scores were elevated for approximately half of both groups, suggesting inflammation does not consistently translate to symptoms. Funding Agencies: CIHR